Exercise medicine for advanced prostate cancer. Issue 3 (September 2017) - Hart, Nicolas H.; Galvão, Daniel A.; Newton, Robert U.
Abstract : Purpose of review: Exercise is a provocative medicine, known for its preventive, complimentary and rehabilitative role in the management of cancer. Impressively, exercise is also emerging as a synergistic and targeted medicine to enhance symptom control, modulate tumour biology and delay disease progression, with the potential to increase overall survival. Given the complex clinical presentation of advanced prostate cancer patients and their omnipresent comorbidities, this review describes the current and potential role of exercise medicine in advanced prostate cancer. Recent findings: Exercise has been shown to be safe, feasible and effective for advanced prostate cancer patients, inclusive of patients with bone metastases; a previously excluded population due to patient and clinician fear of adverse events. Preclinical data provide insight into the ability of exercise to modulate cancer-specific outcomes, may synergistically increase the potency of chemotherapy and radiotherapy and may endogenously and/or mechanically suppress tumour formation, growth and invasion in visceral and skeletal tissue. Epidemiological studies have also shown an association between physical activity and increased survival. Summary: Exercise oncology is rapidly evolving, with impressive possibilities that may directly improve patient outcomes in advanced prostate cancer. Research must focus on translating preclinical trials into human clinical trials and investigate the direct effect of exercise on overall survival.